Uma arquitetura de nomeação para a internet utilizando redes virtuais - Sousa, Joelle Quaini (Universidade Federal de São Carlos, 2007)
Regarding new computational and networking requisites such as wireless networks, mutihoming interfaces, load-balancing mechanisms and several other middleboxes [1] present today, these facts, allied to the static and conservative nature of the Internet and its sheer size turn the capability to correct these problems an almost impossible attempt, as it demands structural changes. In the Internet inception, in the late 70th, neither mobility nor multihoming where foreseen in its original intents. In this sense, the proposition of a novel naming architecture for the Internet to identify univocally services and data, irrespective to its node characteristics, would have an acute changing effect and will allow its elements to be precisely represented and authenticated. In order to achieve these purposes, the use of Virtual Networks was considered as it allows the incremental introduction of new technologies, protocols and applications being itself a more viable alternative when compared to several failed attempts to introduce new structural changes to the Internet [2; 3]. A proposal for a taxonomy for Virtual Networks was described here as a result of a site survey that was conducted to function as subject to this architecture proposition. Besides, a literature investigation of related projects followed by a network testbed of several protocols originated the proposition of a Layered Naming Architecture for the Internet using Virtual Networks.
Keywords: Redes de computação protocolos; DNS; Internet (Redes de computação); Banco de dados; Arquitetura TCP/IP; Overlays; Redes virtuais; Tabelas hash distribuídas; Distributed hash table; TCP/IP architecture; Virtual networks; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO